STAD-TYPE COOPERATIVE LEARNING TO IMPROVE LEARNING OUTCOMES UNDER RING SHOOT - Billy Septian Rizki (Universitas Majalengka, 2022)
The purpose of this study is to improve learning outcomes in basketball games using the student team achievement divisions technique. The type of research used in this research is quasi-experimental research; in this study, it only compares one class, where in this study it only compares the initial test and the final test, while the research stages are determined by how many populations are taken to be the sample, the initial test, the treatment, the final test, the data processing, and the drawing of conclusions. The research design used is known as the one group pretest-posttest design, and the steps are O1 X O2, with O1 representing the pretest (before being given treatment) X, representing the posttest (after being given treatment), and O2 representing the treatment given techniques STAD. Based on data processing and analysis, learning outcomes using the student team achievement divisions technique show a significant increase in learning outcomes under the ring shoot in basketball games. In addition, this approach also emphasizes the placement of technical skills learning in the context of play and gives students the opportunity to see the relevance of basic technical skills in real-life playing situations.